Analisis Yuridis Putusan Pengadilan Negeri Tenggarong Nomor 29/Pid.Sus-Anak/2017/Pn.Trg Tentang Anak Sebagai Pelaku Tindak Pidana Kekerasan Seksual - Putri, Silvi Oktavia Soewito (Indonesian Journal Publisher, 2024)
Cases of criminal acts involving children are very common. One of them is the case of sexual violence committed by minors. This can happen for various reasons. One of them is the lack of supervision from parents, inadequate access to sexual education for children, and also the lack of control over technological developments in internet use. The purpose of this study was to analyze the decision of the Tenggarong District Court Number 29/Pid.Sus-Anak/2017/Pn .Trg concerning Children as Perpetrators of Sexual Violence is in accordance with Law no. 11 of 2012 concerning the Juvenile Justice System. The benefit of this research is that the author hopes that this research can provide insight as a reference and reference material for the community and academics to increase knowledge in enriching the science of juvenile criminal justice. The research method that the author uses is normative juridical using a case approach. The results of this study explain that the judge's consideration of the actions of child perpetrators is sentenced to 1 year in prison and 6 months of job training. However, this does not take into account Law Number 71 paragraph 3 concerning the Juvenile Criminal Justice System. that children cannot be sentenced to cumulative penalties, namely fines and imprisonment. Fines can only be replaced by job training. The analysis of the legal material used is deductive reasoning analysis, namely the preparation using a hypothesis or temporary answer. Meanwhile, this study applies a general to specific pattern.